1997
DOI: 10.1002/(sici)1096-9071(199705)52:1<50::aid-jmv9>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of poliovirus excretion after vaccination of infants with two oral polio vaccines prepared on vero cells or on primary monkey kidney cells

Abstract: A comparative study was designed to assess the bioequivalence of 2 oral poliovaccines (OPV) produced on 2 different cell systems: primary monkey kidney (PMK) cells and the Vero cell line. The Vero cell line has been used to overcome the problem of obtaining a regular supply of high quality monkeys that are devoid of latent viruses. For this study, 9 children were vaccinated with PMK-OPV and 12 children with Vero-OPV. The comparison covered poliovirus excretion, reversion of polioviruses in the 5'-noncoding reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Mexico has recently changed from propagation of OPV seed strains in primary monkey kidney cells to Vero cells (16). However, there are no convincing data that propagation in Vero cells increases the stability of OPV, and indeed, one study showed no modification in the pattern of poliovirus excretion when children vaccinated with OPV propagated in Vero cells were compared with children vaccinated with OPV propagated in primary monkey kidney cells (11). We were unable to confirm the absence of the point mutations by sequencing our samples, due to the low concentrations of virus present.…”
Section: Discussionmentioning
confidence: 76%
“…Mexico has recently changed from propagation of OPV seed strains in primary monkey kidney cells to Vero cells (16). However, there are no convincing data that propagation in Vero cells increases the stability of OPV, and indeed, one study showed no modification in the pattern of poliovirus excretion when children vaccinated with OPV propagated in Vero cells were compared with children vaccinated with OPV propagated in primary monkey kidney cells (11). We were unable to confirm the absence of the point mutations by sequencing our samples, due to the low concentrations of virus present.…”
Section: Discussionmentioning
confidence: 76%
“…High type 3 and type 1 estimates (57,59,70,72) most likely represent an artifact of poor take of the first two tOPV doses or low sample size. (71) The lowest estimate of 0.07 from Cohen-Abbo et al (70) may partially reflect an artifact of the low sensitivity of poliovirus detection at 30 days after the challenge, although the study achieved higher isolation rates for the other serotypes. The remaining estimates provide the best data for relative susceptibility after two or more LPV infections and range from 0.09 to 0.44.…”
Section: One Lpv Infection Two or More Lpv Infections Ipv And Lpvmentioning
confidence: 82%
“…high seropositivity after the first dose. The type 1 data from Ghendon and Sanakoyeva (24) and type 2 data from Mallet et al (71) and Samoilovich et al (72) include only seropositive subjects at the time of challenge after receipt of a single OPV dose, with relative susceptibility estimates ranging from 0.20 to 0.55.…”
Section: One Lpv Infection Two or More Lpv Infections Ipv And Lpvmentioning
confidence: 99%
See 2 more Smart Citations